The initial disinfection of paper-based historic items – Observations on some simple suggested methods. (July 2018) - Karbowska-Berent, J.; Górniak, B.; Czajkowska-Wagner, L.; Rafalska, K.; Jarmiłko, J.; Kozielec, T.
Highlights: The disinfection of mouldy paper-based objects is necessary because it ceases biodeterioration and eliminates viable microorganisms. Tea tree oil turned out to be unacceptable for this disinfection because of causing alterations of paper and media. Vapors of 45% water solution of ethanol turned out efficient against fungi and safe for paper and tested media.